Strain-resolved analysis of hospital rooms and infants reveals overlap between the human and room microbiome. Issue 1 (December 2017) - Brooks, Brandon; Olm, Matthew; Firek, Brian; Baker, Robyn; Thomas, Brian; Morowitz, Michael; Banfield, Jillian
Abstract Preterm infants exhibit different microbiome colonization patterns relative to full-term infants, and it is speculated that the hospital room environment may contribute to infant microbiome development. Here, we present a genome-resolved metagenomic study of microbial genotypes from the gastrointestinal tracts of infants and from the neonatal intensive care unit (NICU) room environment. Some strains detected in hospitalized infants also occur in sinks and on surfaces, and belong to species such asStaphylococcus epidermidis, Enterococcus faecalis, Pseudomonas aeruginosa, andKlebsiella pneumoniae, which are frequently implicated in nosocomial infection and preterm infant gut colonization. Of the 15K. pneumoniae strains detected in the study, four were detected in both infant gut and room samples. Time series experiments showed that nearly all strains associated with infant gut colonization can be detected in the room after, and often before, detection in the gut. Thus, we conclude that a component of premature infant gut colonization is the cycle of microbial exchange between the room and the occupant. It is thought that the hospital environment may contribute to infant microbiome development. Here, Brooks et al. present a genome-resolved metagenomic study of microbial genotypes from the infant gut and from neonatal intensive care unit rooms, showing that some strains are found in both infants and rooms.